The influence of environmental factors on growth, sporulation and pathogenicity of Septoria tritici Desm. and Septoria nodorum Berk. and the pathological response of inoculated wheat varieties - Von Wechmar, Barbara (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1961.